Opportunities Beyond the Anesthesiology Department: Broader Impact Through Broader Thinking. (8th March 2021) - Mathis, Michael R.; Schonberger, Robert B.; Whitlock, Elizabeth L.; Vogt, Keith M.; Lagorio, John E.; Jones, Keith A.; Conroy, Joanne M.; Kheterpal, Sachin
Abstract : Ensuring a productive clinical and research workforce requires bringing together physicians and communities to improve health, by strategic targeting of initiatives with clear and significant public health relevance. Within anesthesiology, the traditional perspective of the field's health impact has focused on providing safe and effective intraoperative care, managing critical illness, and treating acute and chronic pain. However, there are limitations to such a framework for anesthesiology's public health impact, including the transient nature of acute care episodes such as the intraoperative period and critical illness, and a historical focus on analgesia alone—rather than the complex psychosocial milieu—for pain management. Due to the often episodic nature of anesthesiologists' interactions with patients, it remains challenging for anesthesiologists to achieve their full potential for broad impact and leadership within increasingly integrated health systems. To unlock this potential, anesthesiologists should cultivate new clinical, research, and administrative roles within the health system—transcending traditional missions, seeking interdepartmental collaborations, and taking measures to elevate anesthesiologists as dynamic and trusted leaders. This special article examines 3 core themes for how anesthesiologists can enhance their impact within the health care system and pursue new collaborative health missions with nonanesthesiologist clinicians, researchers, and administrative leaders. These themes include (1) reframing of traditional anesthesiologist missions toward a broader health system-wide context; (2) leveraging departmental and institutional support for professional career development; and (3) strategically prioritizing leadership attributes to enhance system-wide anesthesiologist contributions to improving overall patient health.